The description of meaningful work on male kindergarten teachers - Lunadevy, Safira Aida; Murty, Ade Iva; Wiroko, Endro Puspo (Institut Agama Islam Negeri Langsa, 2024)
The number of male kindergarten teachers is significantly lower than that of female kindergarten teachers, despite the fact that male teachers are paternal figures who will contribute to the development of students at school. This research aimed to determine the description of meaningful work among male kindergarten teachers. The subjects of this research were three male kindergarten class teachers with different work experiences. A qualitative approach with a case study design was used in this study. The data were obtained through interviews and analyzed from transcribing to interpreting the data. The research findings stated that all the main subjects had different images regarding how each felt their work was meaningful, especially in the aspect of psychological meaningfulness in work. In the aspect of meaning-making through work, all subjects could understand what could improve their qualities and how to understand themselves and their environment. Lastly, in the aspect of greater good motivations, each subject wanted to be helpful to the school stakeholders or even the family of themselves. This research concluded that the three main subjects generally had different images in making their work as kindergarten teachers meaningful. The research implications are that male kindergarten teachers hopefully can improve their performance, early childhood education units are expected to socialize with the public about the presence of male teachers in kindergartens, and the government is also expected to give more appreciation to kindergarten teachers.